Pharmacological effects of nicotine salts on dopamine release in the nucleus accumbens - Xiaonan Li; Lehua Lu; Ying He; Hui Zhang; Yihui Zhang; Huaquan Sheng; Ming Chen; Ming Chen; Jiexiong Ru; Yihan Gao (Frontiers in Pharmacology, 2023)
With the growing number of individuals regularly using e-cigarettes, it has become increasingly important to understand the psychobiological effects of nicotine salts. Nicotine increases the release of dopamine (DA) into the nucleus accumbens (NAc), causing feelings of satisfaction. However, the differences in the DA-increasing effects of different nicotine salts have not been reported. In this study, we used a G protein-coupled receptor-activated DA fluorescent probe (GRABDA1m) and optical fiber photometric recording equipment to monitor the dynamic changes and kinetics of DA release in the NAc of mice exposed to different e-cigarette aerosols, including nicotine, nicotine benzoate, nicotine tartrate, nicotine lactate, nicotine levulinic acid, nicotine malate, and nicotine citrate. The results of this study were as follows: 1) Different types of nicotine salts could increase the release of DA in the NAc. 2) The slopes and half-effective concentrations of the fitted curves were different, suggesting that each nicotine salt had a difference in the efficiency of increasing DA release with concentration changes. 3) The absorption rates of different nicotine salts containing the same original nicotine concentration were significantly different by measuring the blood nicotine content. The effect of nicotine salts on increasing DA was directly proportional to the blood nicotine level. In conclusion, by observing the effects of nicotine salts on DA release in real time in vivo, differences in the pharmacological effects of nicotine salts are revealed to better understand the mechanism underlying the regulatory effects of nicotine salts on the brain.